Self-Perceived Fibromyalgia Among Female Students and Academicians; A Single City Study - Bisma Ishtiaq; Roha Asif; Misbah Amanat Ali; Wajida Perveen; Ijaz Amin; Laiba Naeem (Journal of Aziz Fatimah Medical and Dental College, 2025)
Objectives: The study aims to analyze the prevelance of self reported fibromyligia syndrome among the female students and teachers and its association with demographic factors.